Biosorption Characteristics and Novel Antifungal Activity of Abrus precatorius Seed Extract - Yasmin, N.; Ulabdin, Z.; Shahid, M.; Sheikh, M.A.; Manzoor, A.; Jamil, A. (Asian Journal of Chemistry, 2015)
Antifungal activity of Abrus precatorius was investigated against a panel of opportunistic fungi Fusarium solani and Alternaria solani. Its biosorption capacity was also characterized in Kaolin clay and wastewaters. Appreciable inhibition zones were formed by crude, supernatant, residue and dialysed samples of Abrus against both the fungi whereas inhibition was retained in 2nd peak of gel filtration. The crude extract exhibited pronounced activity against Fusarium solani with 22 mm zone size and minimum inhibitory concentration (MIC) 10.36 μg/mL. Ethanolic extract also showed significant inhibition with MIC 9.76 μg/mL. The plant seed extracts prepared in distilled water, 5 % NaCl and potassium phosphate buffer showed high coagulative effect in Kaolin clay suspension (turbid water). The plant seed protein coagulated well the particles in the samples. It is worth noting that crude buffer extract showed high activity among all the extracts that is comparable to previously used chemical sorbent (alum) in both low and high turbidity. Based on our findings, we suggest that Abrus precatorius holds promise as a candidate for broad spectrum disease protection, so a resource for new biofungicide and also serves as a good starting material for the synthesis of environment friendly natural coagulant and disinfectant.